Association between Val158Met COMT, TNF-α -857 C>T, TNFR1 36 A>G, IL-1α 4845 G>T and IL-10 -1082 A>G Polymorphisms and Risk of Early-Onset Preeclampsia and Its Complications - Krnjeta, Tijana M; Mirković, Ljiljana; Ignjatović, Svetlana; Tomašević, Dragana; Lukić, Jelena; Topalov, Drina; Majkić-Singh, Nada (Vojnosanitetski pregled, 2018)
Background/Aim. Preeclampsia (PE) belongs to the group of hypertensive disorders in pregnancy with the global average incidence of 2.16%. It is considered as one of the leading causes of maternal and neonatal morbidity and mortality worldwide. The goal of this study was to assess the potential association between Val158Met catechol-o-methyltransferase (COMT), tumor necrosis factor-alpha (TNF-α) -857 C>T, tumor necrosis factor receptor 1 (TNFR1) 36 A>G, interleukin-1alpha (IL-1α) 4845 G>T and interleukin-10 (IL-10) -1082 A>G polymorphisms and risk of early-onset preeclampsia (PE) and its complications. Methods. The study included 47 early-onset PE patients, which were grouped by disease severity and by size for gestational age and 47 control cases. The Val158Met polymorphism was genotyped by polymerase chain reaction – restriction fragment length polymorphism (PCR-RFLP) analysis and inflammatory cytokine polymorphisms by the Sanger sequencing method. Results. The COMT Met allele as well as IL-1α T showed a protective role, decreasing the risk of early-onset PE after age and body mass index (BMI) adjustments. The detected interactions between the COMT Met and IL-10 A alleles, as well as between the COMT Met and TNF-α T alleles were insignificant after age and BMI adjustments. Conclusion. COMT and IL-1α may be used as candidate genes for early-onset PE and its severe form and small for gestational age (SGA) complications.